2009
DOI: 10.1111/j.1365-2044.2008.05858.x
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal compartment syndrome during hip arthroscopy

Abstract: Summary Hip arthroscopy is recognised as a highly effective means of treating joint disorders. The majority of complications associated with hip arthroscopy involve neurovascular traction injury. We report a relatively unusual complication of hip arthroscopy, extravasation of irrigation fluid into the retroperitoneal and intraperitoneal cavities, resulting in abdominal compartment syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…Although most reported cases involve extra-capsular endoscopic procedures (typically release of the psoas tendon) [44][45][46] , the fluid can also escape through capsular incisions especially following large capsulotomies at intra-articular hip arthroscopy 47,48 . Another factor, which has been linked with fluid extravasation, is increase in the surgical time of the procedure 44,47 .…”
Section: Fluid Extravasationmentioning
confidence: 99%
“…Although most reported cases involve extra-capsular endoscopic procedures (typically release of the psoas tendon) [44][45][46] , the fluid can also escape through capsular incisions especially following large capsulotomies at intra-articular hip arthroscopy 47,48 . Another factor, which has been linked with fluid extravasation, is increase in the surgical time of the procedure 44,47 .…”
Section: Fluid Extravasationmentioning
confidence: 99%
“…In intra-capsular hip arthroscopy, the fluid escapes through capsular incisions, 39,40 although most reported cases involve extra-capsular endoscopic procedures (typically release of the psoas tendon) 41-43 or the presence of a fresh acetabular fracture 44 ; however, another group did not report similar problems in a series of 11 fractured hips. 45 Often, but not always, the operating time in these cases has been prolonged.…”
Section: Fluid Extravasationmentioning
confidence: 99%
“…In adults, this technique has been used with increasing frequency, largely based on studies reporting increases in functional outcome measures of up to 10 years [13,14,29,38,57], with complication rates less than 1.5% in several large series [11,13,15,63]. Most complications are minor [15,28,63] (eg, chondral scuffing, temporary neurapraxia, broken instrumentation, fluid management, and undertreatment of hip disorders), with major complications (eg, femoral neck fracture, infection, iatrogenic instability and dislocation, abdominal compartment syndrome) being exceedingly rare [4,24,28,48,65]. Philippon et al reported on 16 adolescent patients who underwent arthroscopy for FAI had improvements in a modified HHS, HOS-sport subset, and HOS-activity of daily living subset of 35, 56, and 36 points, respectively (all scores on a scale of 0-100) [59].…”
Section: Introductionmentioning
confidence: 99%